Prospective MRI-based imaging study to assess feasibility of proton therapy for post-prostatectomy radiation. (2nd July 2016) - Swisher-McClure, Samuel; Yin, Lingshu; Rosen, Mark; Batra, Sonny; Berman, Abigail T.; Both, Stefan; Vapiwala, Neha
Abstract: Purpose/Objectives : To optimize delivery of post-prostatectomy radiation (PPRT) with protons by examining dosimetric effects of variations in physician contouring, organ motion, and patient alignment during a course of PPRT.Material and methods : We enrolled 10 patients receiving PPRT in a prospective imaging study. All patients underwent combined computed tomography (CT)/magnetic resonance imaging (MRI) simulation with endorectal balloon (ERB) and received intensity modulated radiation therapy (IMRT) per institutional standards. Study patients underwent weekly MRI verification scans in the treatment position. Three radiation oncologists contoured clinical target volumes (CTV) on initial and verification scans using two consensus guidelines (RTOG and EORTC). We generated IMRT, double scattering (DS), and pencil beam scanning (PBS) proton plans and examined the dosimetric impact of contour variations, inter-fraction motion, and patient alignment techniques.Results : Inter-observer variations in contouring reduced median CTV coverage (D100) by 0.9% for IMRT plans, 2.8% for DS proton plans, 3.4–4.9% for PBS Proton Plans. Inter-fraction changes in target volumes due to internal organ motion resulted in a median loss of target dose coverage (D98) of 0% with IMRT, 3.5% with DS, and 8.1–8.3% with PBS. Median bladder V65Gy increased during the treatment course with all techniques (6.0–7.5%). Changes in the median rectal V60Gy remained small regardless of the treatment technique (0.5–3.1% increase). Alignment to the ERB after cranio-caudal bony alignment reduced CTV displacement compared to bony alignment alone, and as a result CTV coverage (D98) changed <2% with IMRT, DS, and PBS.Conclusion : Proton-based treatments are more sensitive to changes in inter-fraction organ motion during PPRT compared to IMRT, and therefore motion management and patient alignment methods are critical. Patient alignment using bony anatomy as well as the ERB minimizes displacement of the CTV, and reduces variation in target dose coverage particularly for PBS proton therapy.